Prevalence of Cryptosporidium species among HIV/AIDS patients in Sub Saharan Africa; Systematic Review and Meta-Analysis - Ephrem Awulachew; Kuma Diriba; Aschalew Gemede; Feven Wudneh (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2020)
Background: Cryptosporidium species is increasingly recognized as a leading cause of diarrheal disease with life threatening condition in HIV/AIDS patients. Cryptosporidium species is one of the AIDS defining illnesses and associated with an increased risk of death compared to other AIDS-defining illnesses. Objective: To systematically review prevalence of Cryptosporidium species among HIV/AIDS patients in Sub Saharan Africa. Methods: A comprehensive search of electronic databases was conducted on PubMed, EMBASE, African Journal Online (AJOL) and advanced Google Scholar. The reference lists of all identiﬁed articles were searched for additional studies. Meta-analyses were carried out using review manager 5.3, comprehensive meta-analysis and R software version 3.6.1. Evidence for statistical heterogeneity of results was assessed using Cochrane Q x2 test and I2 statistic. Results: A total of 21 studies were included in the systematic review. Meta-analysis by random effect model showed that the estimated pooled prevalence of Cryptosporidium infection in people with HIV infection was 11 % (678/6,262; 95% CI: 7-16%). We demonstrated that CD4 level was significantly related to Cryptosporidium infection, where the highest risk patients are those with CD4 level < 200 cells/μl (OR: 6.039, 95% CI: 4.441- 8.212, P< 0.0001). The funnel plot demonstrated that there was no publication bias. Conclusion: The results of our meta-analysis show a heavy burden of Cryptosporidium infection among HIV/AIDS patients in sub Saharan Africa (11%).